Intelligent Operating Strategies for Multi-Motor Drive Systems - Strop, Malte; Hölscher, Christian; Zimmer, Detmar (OPT-i 2014. 1st International Conference on Engineering and Applied Sciences Optimization)

Intelligente Betriebsstrategien für Mehrmotorenantriebssysteme - Zimmer, Detmar; Hölscher, Christian; Strop, Malte (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Konzeption von Antriebssystembaukästen auf der Basis von branchenspezifischen Antriebslösungen - Klause, Alexander; Zimmer, Detmar (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

intelligent Drive Module (iDM) - Hölscher, Christian; Zimmer, Detmar

Application of Self-optimizing Systems - Hölscher, Christian; Keßler, Jan Henning; Meyer, Tobias; Rasche, Christoph; Reinold, Peter; Sextro, Walter

Molecular Processes Studied at a Single-Molecule Level Using DNA Origami Nanostructures and Atomic Force Microscopy - Bald, Ilko; Keller, Adrian (Molecules)

SeSAME: Modeling and Analyzing High-Quality Service Compositions - Arifulina, Svetlana; Becker, Matthias; Platenius, Marie Christin; Walther, Sven ({Proceedings of the 29th IEEE/ACM International Conference on Automated Software Engineering (ASE 2014)})
Today, software components are traded on markets in form of services. These services can also be service compositions consisting of several services. If a software architect wants to provide such a service composition in the market for trade, she needs to perform several tasks: she needs to model the composition, to discover existing services to be part of that composition, and to analyze the composition's functional correctness as well as its quality, e.g., performance. Up to now, the architect needed to find and use different tools for these tasks. Typically, these tools are not interoperable with each other. We provide the tool SeSAME that supports a software architect in all of these tasks. SeSAME is an integrated Eclipse-based tool-suite providing a comprehensive service specification language to model service compositions and existing services. Furthermore, it includes modules for service matching, functional analysis, and non-functional analysis. SeSAME is the first tool that integrates all these tasks into one tool-suite and, thereby, provides holistic support for trading software services. Thus, it contributes to a software provider's market success.

Towards Systematic Configuration for Architecture Validation - Becker, Matthias; Becker, Steffen; Besova, Galina; Walther, Sven; Wehrheim, Heike ({Proceedings of the 40th Euromicro Conference on Software Engineering and Advanced Applications (SEAA) (Work in Progress Session)})

Cloud Computing Reduces Uncertainties in Quality-of-Service Matching! - Becker, Matthias; Platenius, Marie Christin; Becker, Steffen ({Proceedings of the 2nd International Workshop on Cloud Service Brokerage (CSB)})
Cloud computing resulted in a continuously growing number of provided software services to be used by consumers. Brokers discover services that fit best to consumers' requirements by matching Qualityof-Service (QoS) properties. In order to negotiate Service-Level Agreements (SLAs), a provider has to determine the provided QoS based on QoS analyses. However, the risk for the provider to violate the SLA is high as the service's actual quality can deviate from the specified QoS due to uncertainties that occur during the provider's quality analysis. In this paper, we discuss current software engineering paradigms like cloud computing and service-oriented computing with respect to the amount of uncertainty they induce into service matching and SLA negotiations. As a result, we explain, why cloud computing reduces such uncertainties.

2.3 Artifact-Centric Requirements Engineering for Self-Adaptive Systems - Knauss, Alessia; Muñoz-Fernández, Juan C.; Castañeda, Lorena; Becker, Matthias; Derakhshanmanesh, Mahdi; Taherimakhsousi, Nina; Heinrich, Robert ({Report from the GI Dagstuhl Seminar 14433: Software Engineering for Self-Adaptive Systems})

Approaching the Cloud: Using Palladio for Scalability, Elasticity, and Efficiency Analyses - Lehrig, Sebastian; Becker, Matthias ({Proceedings of the Symposium on Software Performance (SOSP)})

Feature models supporting trade-off decisions in early mechatronic systems design - Kühn, Arno; Bremer, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (NordDesign 2014, Espoo, Finnland, 27. - 29. Aug. 2014)

Der Spitzencluster it's OWL auf dem Weg zur Industrie 4.0 - Gausemeier, Jürgen; Dumitrescu, Roman; Jasperneite, Jürgen; Kühn, Arno; Trsek, Henning (ZWF - Zeitschrift für Wirtschaftlichen Fabrikbetrieb)

Terrain Classification for Track-driven Agricultural Robots - Mahadhir, Khairul Azmi; Tan, Shing Chiang; Low, Cheng; Dumitrescu, Roman; Amin, Adam Tan Mohd; Jaffar, Ahmed (Procedia Technology)

Specification Technique CONSENS for the Description of Self-optimizing Systems - Dorociak, Rafal; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter (Design Methodology for Intelligent Technichal Systems)

Strategy controlling for innovation clusters - the example of "it's OWL" - Kühn, Arno; Kliewe, Daniel; Dumitrescu, Roman; Gausemeier, Jürgen (ISPIM Conference 2014)

Systematische Berücksichtigung von Fertigungsanforderungen im Model-Based Systems Engineering - Dumitrescu, Roman; Fechtelpeter, Christian; Kühn, Arno (Tag des Systems Engineering, Bremen)

Methodology for the identification of solution patterns within mechatronic systems - Rabe, Martin; Anacker, Harald; Dumitrescu, Roman (Proceedings of the 15th International Workshop on Research and Education in Mechatronics (REM), El Gouna, Egypt)

Collaboration in Model-Based Systems Engineering based on Application Scenarios - Tschirner, Christian; Kaiser, Lydia; Dumitrescu, Roman; Gausemeier, Jürgen (NordDesign 2014)

Optimized process sequences for prototyping of molded interconnect devices - Jürgenhake, Christoph; Fechtelpeter, Christian; Dumitrescu, Roman; Heidsiek, Daniel (Advanced Materials Research)

Method for the Identification and Comparison of Alternative Process Chains Focusing on Economics Efficiency Analysis during the Conceptual Design of Mechatronic Integrated Devices - Schierbaum, Thomas; Gausemeier, Jürgen; Dumitrescu, Roman (Advanced Materials Research)

Virtual Commissioning by Means of an Adaptive Selection of the Modeling Depth - Frieben, Tanja; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE14, Montreal, Québec, Canada)

Methodology for a Partly Automated Parameter Identification for the Validation of Multi-Domain Models - Kruse, Daniel; Schweers, Christoph; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE 2014)

Dynamic Behavior Models and their Modeling Depth in the Design Process of Mechatronic Systems - Lochbichler, Matthias; Oestersötebier, Felix; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE 2014)

Ansätze zur Regelung eines elektronischen Lastemulators für die Hardware-in-the-Loop-Simulation von Antriebsreglern auf Leistungsebene - Kromov, Ivan; Deter, Matthias; Trächtler, Ansgar (SPS IPC Drives)

Optimal Trajectory Planning for Robotic Manipulators Using Discrete Mechanics and Optimal Control - Shareef, Zeeshan; Trächtler, Ansgar (Multi-Conference on Systems and Control (MSC) / 23rd Conference on Control Applications (CCA))

Analysis of high speed bending operations as basis for integrating self-correcting components to increase process reliability - Damerow, Ulf-Hendrik; Borsig, Michael; Tabakajew, Dmitri; Schaermann, Waldemar; Homberg, Werner; Trächtler, Ansgar (Procedia Engineering 81)

Parametrische Modellordnungsreduktion für hierarchische selbstoptimierende Systeme - Krüger, Martin (Workshop GMA-Fachausschuss 1.30)

Subjective Evaluation of Different Motion Cueing Algorithms Implemented on ATMOS Driving Simulator - Al Qaisi, Imad; Zimmermann, Daniel; Kohlstedt, Andreas; Gausemeier, Sandra; Trächtler, Ansgar (Driving Simulation Conference 2014)

Consensus coordination for multiple autonomous intersection management - Wuthishuwong, Chairit; Trächtler, Ansgar (Tagungsband 9. Dortmunder AutoTag)

Modellbasierte Analyse und regelungstechnische Maßnahmen zur Optimierung des Vereinzelungsvorgangs in Bankautomaten - Just, Viktor

Stability of the consensus in the network of multiple Autonomous Intersections Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. 20th International Conference on Automation and Computing (ICAC))

Simultaneous Path Planning and Trajectory Optimization for Robotic Manipulators using Discrete Mechanics and Optimal Control - Shareef, Zeeshan; Trächtler, Ansgar (Robotica)

Consensus Coordination in the Network of Autonomous Intersection Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. 11th International Conference on Informatics in Control Automation and Robotics ICINCO)

Sliding Mode and Continuous Estimation Techniques for the Realization of Advanced Control Strategies for Parallel Kinematics - Flottmeier, Sarah; Olma, Simon; Trächtler, Ansgar (Proceedings of the 19th IFAC World Congress)

Control of Pareto Points for Self-Optimizing Systems with Limited Objective Values - Kessler, Jan Henning; Trächtler, Ansgar (The 19th IFAC World Congress)

Joint Selection Criterion for Optimal Trajectory Planning for Robotic Manipulators Using Dynamic Programming - Shareef, Zeeshan; Trächtler, Ansgar (19th IFAC World Congress)

Analyses of the stress-strain behaviour of SMAs under cyclical loading conditions – implementation of a novel phenomenological constitutive model - Pai, Arathi; Krooß, Philipp; Niendorf, Thomas; Koke, Isabel; Trächtler, Ansgar; Schaper, Mirko (Posterbeitrag ICOMAT - International Conference on Martensitic Transformations, Juli 2014, Bilbao, Spanien)

Concept for a self-correcting sheet metal bending operation

Design and Control of a Vertical Ball Juggling Delta Robot without Visual Guidance - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Trächtler, Ansgar (13th International Conference on Intelligent Autonomous Systems)

Configuration of Mechatronic Systems Using Feature Models - Abrishamchian, Farisoroosh; Trächtler, Ansgar (2nd International Conference on System-Integrated Intelligence)

Selbstkorrigierende Biegeprozesse in der Umformtechnik

Continuous Objective-based Control for Self-Optimizing Systems with Changing Operation Modes - Kessler, Jan Henning; Krüger, Martin; Trächtler, Ansgar (13th European Control Conference (ECC))

Semantische Technologien im Entwurf mechatronischer Systeme: Effektiver Austausch von Lösungswissen in Branchenwertschöpfungsketten - Gausemeier, Jürgen; Trächtler, Ansgar; Schäfer, Wilhelm; Anacker, Harald; Bauer, Frank; Borcherding, Holger; Dziwok, Stefan; Frank, Ursula; Herden, Rudolf; Hoppe, Gerd; Just, Viktor; Kiele-Dunsche, Markus; et al.

Model-based design of self-correcting forming processes - Krüger, Martin; Borsig, Michael; Schaermann, Waldemar (KoMSO Challenge Workshop Math for the Digital Factory)

RAILCAB – THE INNOVATIVE PLATFORM FOR DESIGN AND TEST OF NEW RAILWAY TECHNOLOGIES

Test Rig for the Hardware-in-the-Loop Simulation of Mechatronic Axles - Flottmeier, Sarah; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the 9th International Fluid Power Conference)

A Modelica Contact Library for Idealized Simulation of Independently Defined Contact Surfaces - Oestersötebier, Felix; Wang, Peng; Trächtler, Ansgar (10th International Modelica Conference)

3.1 Sensoren für die digitale Produktion - Klocke, Fritz; Trächtler, Ansgar; Henke, Christian (Integrative Produktion - Industrie 4.0)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)